Penggunaan Kapur Palupuh dan Kapur Rao-Rao pada Asphalt Concrete - Wearing Course - Putri, Elsa Eka; Arasy, Reza Maulana; Martua, Parasian Oscar (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
Indonesia has the many area of the lime production including in the West Sumatra Province. The use of lime as a filler in asphalt mixtures is expected to improve the performance of asphalt mixtures. There are two types of lime used, namely Palupuh and Rao-Rao limestone. This study aims to see the effect of using these 2 types of lime as a filler on Asphalt Concrete-Wearing Course (AC-WC) pavements mixture. The bitumen used is Pen 60/70. Marshall testing was carried out to see the characteristics of the pavement mixture. From Marshall's testing on a pavement without lime, has an optimum asphalt content of 6.015%. Furthermore, with a variation of lime 0%, 25%, 50%, 75%, 100% by weight of filler for both types of lime gave an optimum lime content yield of 50% with an increase in stability of 12.024% and flow of 19.375% for Palupuh lime. Meanwhile, the use of Rao-Rao lime cannot improve the Marshall stability of the AC-WC pavement mixture